We know the derivative of e^{x}, which is e^{x}.
(e^{x})' = e^{x}
We can find the derivative of e^{cscx} using chain rule.
If y = e^{cscx}, find ᵈʸ⁄dₓ.
y = e^{cscx}
Let t = cscx.
Then, we have
y = e^{t}
Now, y = e^{t }and t = cscx. That is, y is a function of t and t is a function of x.
By chain rule, the derivative of y with respect to x :
Substitute y = e^{t} and t = cscx.
Substitute t = cscx.
Therefore,
Kindly mail your feedback to v4formath@gmail.com
We always appreciate your feedback.
©All rights reserved. onlinemath4all.com
Jun 13, 24 03:21 AM
Jun 13, 24 02:35 AM
Jun 13, 24 02:12 AM